2021
DOI: 10.1002/bco2.91
|View full text |Cite
|
Sign up to set email alerts
|

Performance of prostate health index and PSA density in a diverse biopsy‐naïve cohort with mpMRI for detecting significant prostate cancer

Abstract: Objective To compare Prostate Health Index (PHI) and prostate‐specific antigen (PSA) density as secondary tests after multiparametric magnetic resonance imaging (mpMRI) in improving the detection accuracy of Gleason grade group (GG) 2‐5 prostate cancer (PCa) and in decreasing unnecessary biopsies in a multiethnic biopsy‐naïve population. Methods From February 2017 to February 2020, we recruited consecutive biopsy‐naïve men in participating urology clinics for elevated PSA levels. They all had a PHI score, mpMR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
(44 reference statements)
1
4
0
Order By: Relevance
“…Following mpMRI, most of the patients in our study group had PIRADS 4 and 5 score lesions (74%) while only 26% had PIRADS 3 lesions which is similar to other reports [ 20 , 21 , 22 ]. However, in contrast to other studies, we found no significant correlation between the PIRADS score and PSA values.…”
Section: Discussionsupporting
confidence: 91%
“…Following mpMRI, most of the patients in our study group had PIRADS 4 and 5 score lesions (74%) while only 26% had PIRADS 3 lesions which is similar to other reports [ 20 , 21 , 22 ]. However, in contrast to other studies, we found no significant correlation between the PIRADS score and PSA values.…”
Section: Discussionsupporting
confidence: 91%
“…At a 90% sensitivity, the PHI's specificity was 58.3%, potentially avoiding 77 cases (49%) of unnecessary biopsy 22 . The usefulness of PHI has been confirmed by several studies conducted in various ethnic groups and regions 23–25 . It is essential to determine population‐specific reference ranges and cutoff values for the PHI to optimize its diagnostic utility in different ethnic groups and regions.…”
Section: Discussionmentioning
confidence: 97%
“…22 The usefulness of PHI has been confirmed by several studies conducted in various ethnic groups and regions. [23][24][25] It is essential to determine population-specific reference ranges and cutoff values for the PHI to optimize its diagnostic utility in different ethnic groups and regions. A multicenter study involving nine clinical sites in Europe and Asia demonstrated that in Asian populations, implementing a threshold of PHI > 30 could potentially avoid 56% of biopsies and 33% of Gleason 6 PCa diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…The additional benefits of PHI over PSAD in MRI-guided biopsies have been reported in a few studies with sample sizes of around 100 or fewer PI-RADS 3 cases. 9,[16][17][18][19][20] The optimal PHI cutoff and reference ranges specifically for each PI-RADS score could not be defined due to limited sample sizes. PHID has also been shown to perform better than PHI, PSAD, and PSA in csPCa predictions.…”
Section: Discussionmentioning
confidence: 99%